Analisis Kemampuan Pemecahan Masalah Matematika Siswa Kelas XI SMK Pada Materi Trigonometri - Jvana Wahyu Pratami; Nabilla Nabilla (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The aim of this research is to explore students' problem solving abilities in understanding trigonometry concepts. This research is qualitative research with a case study method. This research was conducted on class XI students at one of the private vocational schools in Tangerang City, Banten, totaling 35 students. Data obtained from the results of written tests and interviews conducted by researchers. In this study, researchers analyzed students' abilities in answering Trigonometry questions using constant comparative analysis techniques which consisted of four stages, namely data reduction, data categorization, data synthesis, and working hypothesis.